A reliability approach to fatigue crack propagation analysis of ship structures in polar regions. (November 2021) - Zhao, Weidong; Leira, Bernt Johan; Feng, Guoqing; Gao, Chao; Cui, Ting
Abstract: Fatigue is a common failure mode in ship structures. For structures with an initial crack, the fatigue crack propagation behavior needs to be considered. The purpose of this study is to establish a procedure for analysis of fatigue crack propagation of ship structures in combination with reliability methods. The stress intensity factor (SIF) and geometry correction factor are calculated by means of finite element analysis. Validation for the SIF calculation is achieved by comparing the computed results with those based on related solutions. Since fatigue damage usually occurs in weld areas, the effect of such components on the fatigue crack propagation behavior was also considered in this work. The Paris law in combination with the Monte Carlo technique are employed for the fatigue crack propagation analysis in this study. Reliability updating based on inspection for cracks is also carried out. A computer program was developed for the purpose of fatigue crack propagation analysis within the framework of reliability methods. An application example of fatigue crack propagation in relation to the hull of the icebreaker Xuelong 2 is presented. The sensitivity of the procedure to key analysis parameters (sample size, initial crack size) is also considered. Finally, the effect of low temperatures on the computed results is also analyzed. Highlights: Surface crack propagation of welded joints is simulated by the computer program ABAQUS. Reliability updating based on inspection of cracks is carried out. A reliability-based algorithm (named FCPR) for fatigue crack propagation evaluation within ship components is developed. Fatigue crack propagation of the icebreaker Xuelong 2 at low temperatures was analyzed by applying the FCPR program.